2021
DOI: 10.1039/d1ra00845e
|View full text |Cite|
|
Sign up to set email alerts
|

Electrochemical investigation and amperometry determination iodate based on ionic liquid/polyoxotungstate/P-doped electrochemically reduced graphene oxide multi-component nanocomposite modified glassy carbon electrode

Abstract: Constructing a sensitive electrochemical sensor based on (bdpy)SiW11Ni/P-ERGO/GCE for IO3− detection at the nanomolar level with noticeable selectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 89 publications
(166 reference statements)
0
14
0
Order By: Relevance
“… Sharifi et al (2021 ) reported a modified GCE with a tetra-component nanocomposite consisting of a [1,10-(1,4-butanediyl) dipyridinium] ionic liquid (bdpy), the Keggin-type SiW 11 O 39 Ni(H 2 O) (abbreviated as SiW 11 Ni), and Phosphorus-doped electrochemically reduced graphene oxide (P-rGO), by electrodeposition technique for iodate determination. The presence of bdpy provided an additional advantage for increasing the loading of POM, improving the stability of the nanocomposite due to the strong electrostatic attraction between SiW 11 Ni and positively charged bdpy.…”
Section: Polyoxometalates Functionalized Sensorsmentioning
confidence: 99%
“… Sharifi et al (2021 ) reported a modified GCE with a tetra-component nanocomposite consisting of a [1,10-(1,4-butanediyl) dipyridinium] ionic liquid (bdpy), the Keggin-type SiW 11 O 39 Ni(H 2 O) (abbreviated as SiW 11 Ni), and Phosphorus-doped electrochemically reduced graphene oxide (P-rGO), by electrodeposition technique for iodate determination. The presence of bdpy provided an additional advantage for increasing the loading of POM, improving the stability of the nanocomposite due to the strong electrostatic attraction between SiW 11 Ni and positively charged bdpy.…”
Section: Polyoxometalates Functionalized Sensorsmentioning
confidence: 99%
“…6C, peak I, which corresponds to HER, is only seen at pH 0.5 (curve a). This phenomenon can be due to the stability of POMs-based modied electrodes 9,10 and also the performance of HER at acidic pH. 83,84 Therefore, pH 0.5 was considered the optimal pH, and further studies were performed at this pH.…”
Section: Electrochemical Activity Of Pw 12 /Mof/p@ergo/gcementioning
confidence: 99%
“…Among the carbon materials, graphene extensively studied in nanotechnology elds due to its excellent chemical stability, high surface area, extraordinary conductivity, and good mechanical properties. 10,12 Graphene was discovered at Manchester University by Andre Geim and Kostya Novoselov in 2004. 52 It is an allotrope of carbon-containing a single layer of atoms arranged in a twodimensional (2D) hexagonal lattice nanostructure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations